Lean construction e obras públicas: um mapeamento sistemático na literatura - Weber, Lucas Eduardo; Santos, Débora de Gois (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Public enterprises are of utmost importance for the development of a nation. However, its construction is usually characterized by several problems such as non-compliance with the deadline, the value and the poor quality presented. Thus, the applicability of the principles of Lean Construction in the public sector comes with the objective of mitigating these problems. The objective of this research was to provide an overview of research involving the themes of Lean Construction and Public Works through a Systematic Mapping Study. As a result, it was evidenced that there is little research that addresses the two themes simultaneously, but with growth of publications in recent years. Research focuses on publications in the International Group for Lean Construction, the countries with the most publications located in the Northern Hemisphere such as the United States, Norway and the United Kingdom, and the vast majority of studies are based on case studies. Thus, the need to disseminate Lean Construction and its applications in the public sector remains proven.